2002
DOI: 10.1021/jm0208875
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Pharmacophore for Drugs Inducing the Long QT Syndrome:  Insights from a CoMFA Study of HERG K+ Channel Blockers

Abstract: In this paper, we present a pharmacophore for QT-prolonging drugs, along with a 3D QSAR (CoMFA) study for a series of very structurally variegate HERG K(+) channel blockers. The blockade of HERG K(+) channels is one of the most important molecular mechanisms through which QT-prolonging drugs increase cardiac action potential duration. Since QT prolongation is one of the most undesirable side effects of drugs, we first tried to identify the minimum set of molecular features responsible for this action and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
319
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 376 publications
(338 citation statements)
references
References 26 publications
19
319
0
Order By: Relevance
“…In this study, molecular weight (M W ), molecular fractional polar surface area (FPSA), and lipophilicity (ALogP) were used. We also calculated the pK a of the most positive basic nitrogen (pK a basic) based on previous pharmacophore models [7,14,15] . These four molecular properties were used as simple molecular descriptors for hERG blockage modeling and were calculated with the "Calculate Molecular Properties" protocol within Discovery Studio (version 3.0; Accelrys, San Diego, CA, USA) and components in Pipeline Pilot (version 7.5; Accelrys, San Diego, CA, USA).…”
Section: Calculation Of Molecular Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, molecular weight (M W ), molecular fractional polar surface area (FPSA), and lipophilicity (ALogP) were used. We also calculated the pK a of the most positive basic nitrogen (pK a basic) based on previous pharmacophore models [7,14,15] . These four molecular properties were used as simple molecular descriptors for hERG blockage modeling and were calculated with the "Calculate Molecular Properties" protocol within Discovery Studio (version 3.0; Accelrys, San Diego, CA, USA) and components in Pipeline Pilot (version 7.5; Accelrys, San Diego, CA, USA).…”
Section: Calculation Of Molecular Propertiesmentioning
confidence: 99%
“…In our study, we found that molecules with larger ALogP and M W but smaller FPSA are more likely to be blockers, which could be ascribed to the large pore size in hERG as well as the lipophilic character of the pore cavity [37] . Generally, a nitrogen positive ionizable center has been considered a common feature for many hERG blockers [7,50,51,52] . We calculated the pK a value of the most basic nitrogen of compounds (pK a _basic) and found that the pK a _basic of nonblocking molecules is likely to be zero.…”
Section: Molecular Features Important For Hergmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a description of the physicochemical features of the drug binding site would complement pharmacophore models (8,9) of drugs that block hERG channels and define the molecular basis for receptor fields predicted by these models. Toward this goal, we have used site-directed mutagenesis and voltage clamp analysis of mutant channels expressed in Xenopus oocytes to elucidate the molecular mechanisms of hERG channel block by structurally diverse drugs, including MK-499, cisapride, terfenadine, vesnarinone, chloroquine, and quinidine (10 -13).…”
Section: Long Qt Syndrome (Lqts)mentioning
confidence: 99%
“…Pharmacophore models predict that important features of potent hERG channel blockers are 1) a basic nitrogen that is usually protonated at physiological pH and 2) three hydrophobic centers of mass (centroids) arranged in a specific spatial pattern around the centrally located nitrogen (8,9). For many potent hERG blockers, these centroids are aromatic groups.…”
Section: Long Qt Syndrome (Lqts)mentioning
confidence: 99%